Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/etc.5045
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolating Acute Contact Bee Sensitivity to Insecticides Based on Body Weight Using a Phylogenetically Informed Interspecies Scaling Framework

Abstract: Plant protection products, including insecticides, are important for global food production but can have adverse effects on nontarget organisms including bees. Historically, research investigating such effects has focused mainly on the honeybee (Apis mellifera), whereas less information is available for non-Apis bees. Consequently, a comprehensive hazard (sensitivity) assessment for the majority of bees is lacking, which in turn hinders accurate risk characterization and consequently bee protection. Interspeci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 61 publications
0
21
0
1
Order By: Relevance
“…For C. incertus and D. gazella , the effects of chemical pollutants on SST allometric relationships have not been well documented so far. However, it has been reported that allometric relationships in other insect traits can be altered by environmental pollution (Pamminger, 2021; Souza et al, 2018) and unfavourable developmental conditions (Emlen, 1997; Macagno et al, 2009; Stern & Emlen, 1999). For example, Souza et al (2018) reported that the use of the insecticides teflubenzuron and lufenuron alters wing and leg allometry of the wasp Trichogramma pretiosum and selects for individuals of large sizes and negative allometries ( b < 1) when they are usually isometric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For C. incertus and D. gazella , the effects of chemical pollutants on SST allometric relationships have not been well documented so far. However, it has been reported that allometric relationships in other insect traits can be altered by environmental pollution (Pamminger, 2021; Souza et al, 2018) and unfavourable developmental conditions (Emlen, 1997; Macagno et al, 2009; Stern & Emlen, 1999). For example, Souza et al (2018) reported that the use of the insecticides teflubenzuron and lufenuron alters wing and leg allometry of the wasp Trichogramma pretiosum and selects for individuals of large sizes and negative allometries ( b < 1) when they are usually isometric.…”
Section: Discussionmentioning
confidence: 99%
“…Although sexual selection promotes the evolution of SST with strong positive allometry (Eberhard et al, 2018;Kodric-Brown et al, 2006;Voje, 2016), it has also been reported that stressful environments can modify the magnitude and sign of allometric relationships (Pamminger, 2021;Souza et al, 2018).…”
mentioning
confidence: 99%
“…Standard laboratory‐based toxicity studies with honey bee larvae and adults are conducted in the context of tier 1 assessments. A growing number of laboratory‐based toxicity studies with bee species other than the honey bee can inform cross‐species analysis of intrinsic sensitivities and possible test designs with other species (Arena and Sgolastra 2014; Thompson 2016; Heard et al 2017; Thompson and Pamminger 2019; Eeraerts et al 2020; Ceuppens et al 2015; Pamminger 2021). If tier 1 indicates that a risk cannot be excluded based on the conservative assumptions, higher tier assessments must be conducted, including semifield (tunnel) and field studies (Peters et al 2016; Ruddle et al 2018; Franke et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Scaling approaches based on body weight can be used to estimate both hazard and exposure parameters in a range of organisms and some are currently utilized in ecological risk assessment schemes (Davidson, Parker, & Beliles, 1986;EFSA, 2009;Mineau et al, 2001;Mineau, Collins, & Baril, 1996;Pamminger, 2021;Urban & Urban, 1986). Such methods offer a clear alternative to experimental investigations in cases where such approaches are not feasible (e g. number of species) or desirable (e.g vertebrate testing).…”
Section: Accepted Articlementioning
confidence: 99%